Complex haemostatic abnormalities as a cause of bleeding after neurosurgery in a patient with Gaucher disease. (18th April 2014) - Mitrovic, Mirjana; Elezovic, Ivo; Grujicic, Danica; Miljic, Predrag; Suvajdzic, Nada
Abstract: We report a treatment-naïve patient with Gaucher disease (GD) who experienced repeated bleeding after three neurosurgeries for a brain tumour, identified as an oligoastrocytoma. The patient had normal values on basic haemostatic tests: prothrombin time, 75–105%; activated partial thromboplastin time, 30.3–34 s; and mild thrombocytopaenia, 96–115 × 10 9  cells/l. However, additional tests showed mild von Willebrand factor (vWF) deficiency (vWF antigen, 56%; vWF ristocetin cofactor, 49%; factor VIII [FVIII], 54%) and abnormal collagen-mediated platelet aggregation (0.45–0.55). Bleeding control was achieved after vWF/FVIII concentrate and platelet transfusions. This case raises questions about the safe platelet count and basic haemostatic tests for assessing bleeding risk in patients with GD prior to surgery. In patients with GD, a minimum haemostatic evaluation should include platelet count and basic haemostatic tests such as fibrinogen, prothrombin time, activated partial thromboplastin time as well as platelet function tests and assessing vWF and FVIII levels. Specific coagulation factors or platelet function deficiencies should be corrected with factor concentrates or platelet transfusions.